Toxicity assessment of molybdenum slag as a mineral fertilizer: A case study with pakchoi (Brassica chinensis L.). (February 2019) - Chen, Dong; Meng, Zhong-wen; Chen, Yi-ping
Abstract: Large quantities of molybdenum (Mo) slag are generated as a by-product during mining and smelting, which not only occupy huge stretches of arable land and natural habitats but also threaten the local ecosystem and environment. How to recycle this Mo slag is becoming an urgent issue. Here, we reported the toxicity assessment of Mo slag as a mineral fertilizer for slag recycling in agricultural practices. The results showed the following: (1) Lower rates of slag (1.0%, 2.5%, and 5.0%) fertilization, especially 5.0% slag, increased the activities of antioxidant enzymes (superoxide dismutase, catalase, and peroxidase), the contents of chlorophyll, and both the maximum quantum yield and quantum efficiency of photosystem II; decreased the content of malondialdehyde and the non-photochemical quenching of photosystem II; and eventually increased the height, leaf area, and biomass of pakchoi seedlings; (2) Higher rates (7.5% and 10.0%) of Mo slag application resulted in a reduction in the aforementioned physiological and morphological parameters (except for peroxidase activity) of pakchoi seedlings; and (3) Although fertilization with 5.0% slag increased the accumulation of the non-essential elements arsenic (As), lead (Pb), and cadmium (Cd) in pakchoi seedlings, their contents were still lower than the maximum levels of the Codex Alimentarius Commission, European Union, and standards of China. From the perspectives of plant nutrition and food safety, our results showed that Mo slag fertilization at rates lower than 5.0% can be applied as a mineral fertilizer for pakchoi grown on calcareous soils. Graphical abstract: Highlights: Low rates of Mo slag improve the physiology and growth of pakchoi seedlings. High rates of Mo slag stunt pakchoi seedling growth and yield. Contents of non-essential elements in seedlings meet the maximum levels in food standards. Low rates of Mo slag can be a potential mineral fertilizer in agricultural practices.